Characteristics of a novel treatment system for linear accelerator–based stereotactic radiosurgery. (8th July 2015) - Wen, Ning; Li, Haisen; Song, Kwang; Chin‐Snyder, Karen; Qin, Yujiao; Kim, Jinkoo; Bellon, Maria; Gulam, Misbah; Gardner, Stephen; Doemer, Anthony; Devpura, Suneetha; Gordon, James; et al.
Abstract : The purpose of this study is to characterize the dosimetric properties and accuracy of a novel treatment platform (Edge radiosurgery system) for localizing and treating patients with frameless, image‐guided stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT). Initial measurements of various components of the system, such as a comprehensive assessment of the dosimetric properties of the flattening filter‐free (FFF) beams for both high definition (HD120) MLC and conical cone‐based treatment, positioning accuracy and beam attenuation of a six degree of freedom (6DoF) couch, treatment head leakage test, and integrated end‐to‐end accuracy tests, have been performed. The end‐to‐end test of the system was performed by CT imaging a phantom and registering hidden targets on the treatment couch to determine the localization accuracy of the optical surface monitoring system (OSMS), cone‐beam CT (CBCT), and MV imaging systems, as well as the radiation isocenter targeting accuracy. The deviations between the percent depth‐dose curves acquired on the new linac‐based system (Edge), and the previously published machine with FFF beams (TrueBeam) beyond D max were within 1.0% for both energies. The maximum deviation of output factors between the Edge and TrueBeam was 1.6%. The optimized dosimetric leaf gap values, which were fitted using Eclipse dose calculations and measurements based on representative spine radiosurgery plans, were 0.700 mm and 1.000 mm, respectively. For the conical cones, 6X FFF has sharper penumbra ranging from 1.2 − 1.8   mm (80%‐20%) and 1.9 − 3.8   mm (90%‐10%) relative to 10X FFF, which has 1.2 − 2.2   mm and 2.3 − 5.1   mm, respectively. The relative attenuation measurements of the couch for PA, PA (rails‐in), oblique, oblique (rails‐out), oblique (rails‐in) were: − 2.0 %, − 2.5 %, − 15.6 %, − 2.5 %, − 5.0 % for 6X FFF and − 1.4 %, − 1.5 %, − 12.2 %, − 2.5 %, − 5.0 % for 10X FFF, respectively, with a slight decrease in attenuation versus field size. The systematic deviation between the OSMS and CBCT was − 0.4 ± 0.2   mm, 0.1 ± 0.3   mm, and 0.0 ± 0.1   mm in the vertical, longitudinal, and lateral directions. The mean values and standard deviations of the average deviation and maximum deviation of the daily Winston‐Lutz tests over three months are 0.20 ± 0.03   mm and 0.66 ± 0.18   mm, respectively. Initial testing of this novel system demonstrates the technology to be highly accurate and suitable for frameless, linac‐based SRS and SBRT treatment. PACS number: 87.56.J‐